Analisis Performa Homestay Desa Wisata untuk Mewujudkan Standarisasi di Kabupaten Kulon Progo - Wijayanti, Ani; Dewi, Ike Janita (Lasigo Akademia Indonesia, 2023)
Homestay is one of the mandatory accommodations in a tourist village. Optimal homestay management is a guide for every tourist to get comfort during their stay. This study aims to examine the performance of homestays in the tourist village of Kulon Progo through three variables: product, service and management. This study used a quantitative descriptive approach, with scoring and reduction data analysis techniques. The research samples were 11 tourist villages in Kulon Progo. Purposive sampling technique was used to select tourist villages based on their categories. The results showed two homestay class categories, namely classes 1 and 2. Product variables have the highest performance, while service and management have almost the same performance and are still relatively low. Performance indicators that are considered to be still low, namely digital-based services and administration. The performance of the homestay is often not in line with the classification of tourist villages. The survey results show advanced tourism villages have lower homestay performance than the pioneer and developing tourism villages. The research implication provides an overview of homestay performance in Kulonprogo as a reference in improving homestay standardization.